Snailase: A Promising Tool for the Enzymatic Hydrolysis of Flavonoid Glycosides From Plant Extracts - Kornpointner, Christoph; Scheibelreiter, Jakob; Halbwirth, Heidi (Frontiers in Plant Science, 2022)
Plants typically contain a broad spectrum of flavonoids in varying concentrations. As a rule, several flavonoid classes occur in parallel, and, even for a single flavonoid, divergent glycosylation patterns are frequently observed. This can be challenging in studies in which the distribution between flavonoid classes, or features that are not affected by glycosylation patterns, are addressed. Herein, we present a fast and reliable method for enzymatic hydrolysis of flavonoid glycosides from plant extracts using the commercial enzyme mix snailase, which provided the highest aglycone yields of all investigated flavonoids (aurones: leptosidin, maritimetin, sulfuretin; chalcones: butein, lanceoletin, okanin, phloretin; dihydroflavonols: dihydrokaempferol; flavanones: eriodictyol, hesperetin; flavones: acacetin, apigenin, diosmetin, luteolin; flavonols: isorhamnetin, kaempferol, myricetin, quercetin; isoflavones: biochanin A, formononetin, genistein) from methanolic extracts of nine plants (Bidens ferulifolia, Coreopsis grandiflora, Fagus sylvatica, Malus × domestica, Mentha × piperita, Petunia × hybrida, Quercus robur, Robinia pseudoacacia and Trifolium pratense) in comparison to four other enzymes (cellobiase, cellulase, β-glucosidase and pectinase), as well as to acidic hydrolysis by hydrochloric acid.